Post-COVID Tourism Recovery Strategy for Tourism Villages: Multi-Stakeholder Participatory Approaches - Mimin Sundari Nasution; Al Fauzi Rahmat; Tito Handoko; Fajar Rahmanto; Mayarni Mayarni (Journal of Contemporary Governance and Public Policy, 2023)
This article examines recovery strategies in post-COVID-19 tourism villages in Bantul, Yogyakarta, Indonesia, utilising a rural tourism resilience approach involving multi-stakeholder participation. This qualitative study collected data through interviews, literature, social media, and local news online observations. The data obtained were then analysed with the help of a code from NVivo 12 Plus to visualise the multi-stakeholder network in the five tourism village recovery strategies through the sociogram network, group queries, and concept mapping queries. The results of this study reveal the following: First, the five tourist villages have different ways of getting back on their feet and getting more substantial for a massive recovery. Second, all government levels strongly support accelerating the five tourist villages' recovery via various media promotions of the four (Tembi, Kakilangit, Kebonagung, and Kampung Santan), except for Lopati's tourism village destinations. In addition, the two villages, in terms of the resilience of social networks, mostly need support in increasing institutional capacity (Kampung Santan and Lopati), fostering collaboration, and requiring creativity. Therefore, post-COVID, mechanisms for development and new ideas in two tourist villages (Lopati and Kampung Santan) were relatively noticeable. Some tourism villages still need leaders for programmes and activities. Further, the government's persistence in popularising tourist villages requires further improvement through media promotion, tourism awareness groups, and participation in the tertiary sector.